2002
DOI: 10.1210/mend.16.7.0866
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Deoxyribonucleic Acid Binding Domain of the Vitamin D Receptor Abrogates Genomic and Nongenomic Functions of Vitamin D

Abstract: The vitamin D hormone 1,25-dihydroxyvitamin D(3) [1,25-(OH)(2)D(3)], the biologically active form of vitamin D, is essential for an intact mineral metabolism. Using gene targeting, we sought to generate vitamin D receptor (VDR) null mutant mice carrying the reporter gene lacZ driven by the endogenous VDR promoter. Here we show that our gene-targeted mutant mice express a VDR with an intact hormone binding domain, but lacking the first zinc finger necessary for DNA binding. Expression of the lacZ reporter gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
139
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 235 publications
(149 citation statements)
references
References 48 publications
7
139
3
Order By: Relevance
“…This constellation of abnormalities is observed in humans with VDR mutations in the inherited disorder vitamin D-dependent rickets type II (also called hereditary vitamin D-resistant rickets) (23). Rescue of this phenotype has been successfully accomplished with a high calcium, high phosphorus, high lactose diet administered for at least 1 month after weaning (22,24). Consequently, it has been postulated that the major action of the VDR in skeletal growth, maturation, and remodeling is its role in intestinal calcium absorption (25).…”
mentioning
confidence: 99%
“…This constellation of abnormalities is observed in humans with VDR mutations in the inherited disorder vitamin D-dependent rickets type II (also called hereditary vitamin D-resistant rickets) (23). Rescue of this phenotype has been successfully accomplished with a high calcium, high phosphorus, high lactose diet administered for at least 1 month after weaning (22,24). Consequently, it has been postulated that the major action of the VDR in skeletal growth, maturation, and remodeling is its role in intestinal calcium absorption (25).…”
mentioning
confidence: 99%
“…Osteoblasts, which are secretory cells, produce a variety of bone matrix proteins and actively participate in the mineralization process under the influence of hormones involved in mineral metabolism, such as 1,25D. Recently, several strains of functional VDR knockout (KO) mice have been created by means of deletion of selected portions of the VDR gene (10)(11)(12)(13). They constitute a valuable tool for the study of a vast range of physiological conditions that arise from an impaired 1,25D physiology.…”
mentioning
confidence: 99%
“…Control cells responded within seconds to 1,25-(OH) 2 D 3 by increasing intracellular calcium concentration. The profile of the calcium response, the dose-response curve (maximal effect at 100 pM), and the inhibition of the response by the two L-type calcium channel blockers (verapamil and nifedipine) and the PLC inhibitor (U-73122) were identical to those found in other cell types such as osteoblasts, enterocytes, and parathyroid cells (7,20,21,36). Interestingly, fibroblasts bearing the K45E mutation showed no calcium response to 1,25-(OH) 2 D 3 , whereas fibroblasts bearing the W286R mutation showed a calcium response similar to controls as regards time course profile, the active range of 1,25-(OH) 2 D 3 concentrations, and the inhibitory effects of calcium channel and PLC inhibitors.…”
Section: Discussionmentioning
confidence: 65%
“…Cells from patients 2 and 3, with a W286R mutation in the ligandbinding domain, were selected as models with markedly destabilized ligand binding capacity, as shown by previous biological studies (26) and as suggested by x-ray crystal structure analysis of the mutated VDR. 2 In the three cases, the remaining portion of the VDR gene was normal, unlike in the previously reported osteoblast models, which bore large deletions of the VDR gene (21,22).…”
mentioning
confidence: 58%
See 1 more Smart Citation